Cytological and Histological Effect of Paracetamol on the Testis and Liver in Albino Mice Mus musculus - W, Qader S.; O., Othman G. (Sulaimani Journal for Pure and Applied Sciences, 2014)
The purpose of this study is to evaluate the acute toxicity effects of pure paracetamol tablets on laboratory mice. In this study Mus musculus mice (6-8) weeks old were used. The toxicity effects were evaluated on fifteen mice, in which they were divided equally into three groups, each one consists of five individual mice. The first group was labeled as a vehicle group and received 5mL/kg DW. The second and third groups were labeled as experimental groups which received 2 g/kg and 5 g/kg of paracetamol respectively. After fifteen days the animals were examined for toxicity signs and then the liver and testis were processed for histological examinations. Furthermore, the sperm abnormalities were recorded. The results of this study demonstrated that the low dose did not show any morphological changes while some changes such as shivering, nausea and mortality were manifested after administration of high dose of paracetamol. Many histological changes have been observed after high dose treatment of paracetamol, the frequencies of abnormal sperm were increased as well. Therefore, Paracetamol, which is believed to be a strong pain killer for the hangover headache may damage liver and testis when consumes beyond the recommended dose.
Keywords: Paracetamol Histology Hepatotoxicity Testicular toxicity and Sperm abnormalities